Reduction of Voltage Fluctuations in Electrical Networks Supplying Motors with a Rapidly Changing Load by Installing Longitudinal Compensation Batteries - Basmanov V.G.; Kalinina E.A.; Cherepanov V.V. (Problems of the Regional Energetics, 2023)
The article deals with the reduction of voltage fluctuations in electrical networks of industrial enterprises with the help of longitudinal compensation batteries. The purpose of the article is to develop a method for calculating the optimal parameters of the longitudinal compensation installation, which makes it possible to perform calculations using numerical characteristics of the range of changes in the voltage and flicker dose. To achieve this goal, it is necessary to solve the following tasks: to develop a method for selecting the parameters of reducing voltage fluctua-tions, taking into account the random nature of the change in the parameters of network modes; using the proposed method, to develop a calculation method that allows choosing optimal pa-rameters of capacitor units. The most significant result is the experimental and theoretical con-firmation that the proposed method for selecting the parameters of longitudinal compensation batteries, taking into account the random nature of the change in the flicker dose, makes it pos-sible to effectively apply longitudinal compensation to reduce voltage fluctuations in electrical networks of industrial enterprises with a rapidly changing load. The significance of the results is proved by the fact that the proposed method makes it possible to select a longitudinal compensation installation to limit voltage fluctuations at the design stage, thereby ensuring the quality of electric energy in networks with consumers having a rapidly changing load. The resulting calcu-lation method is planned to be used in distribution electrical networks when performing tech-nical measures to ensure the quality of electrical energy.